IoT based air quality monitoring system - Kunaka, Tinashe E (2020)
The ultimate goal of this project was on developing an Internet of Things (IoT) based air pollution monitoring system. This document gives stage by stage procedures that the developer undertook in coming up with the system. The developer undertook an assessment and the results showed that air pollution has alarming effects. Its effects cause a lot of human diseases which include respiratory and heart conditions amongst other body threats. The objectives of this project are to monitor air quality as the detects harmful gases like, carbon monoxide, Sulphur dioxide and nitrogen oxide, to trigger devices such as buzzer and a fan when the pollution levels go beyond and to show a pattern of the air quality components periodically on the web platform. Components used to come up with the system include Arduino Uno microcontroller, MQ135 gas sensor, 16*2 liquid crystal display (LCD), ESP8266 Wi-Fi module, 10 K potentiometer, buzzer and a fan. Key findings within the study were the ability of the system to sound an alarm using a buzzer when harmful gases are detected and ventilation fan will turn on to extract the air. In the first chapter, the background study, system goals, methods and tools used to develop the system, delimitations, research limitations, and research significance were discussed. The second chapter assessed the existing work versus the earlier work. The chapter represented the existing system that surmount the earlier problems. In the methodology chapter, the components that were used to come up with the system were discussed. The design phase of the system illustrated how the system was designed. Lastly the implementation phase, system testing, installation and maintenance were conducted.